Stupidity During the Reformation (Global Journal of Human-Social Science, 2019)
At the same time that people were turning away from theological truths and looking outward at the world, those truths were undergoing dramatic revision as both the Christian religion in particular and Western Civilization in general were thoroughly reformed. In the early sixteenth century, with religious man seeking biblical answers to theological problems, Christianity underwent a number of soul searching revisions which were essentially conservative in nature efforts to go back to times before the Church became corrupted. Meanwhile, with Renaissance Man seeking human answers to temporal questions and functional solutions to real problems, the secular religions of capitalism and nationalism were taking shape. Thus, as Christian theology was being redefined, the Bible reinterpreted and the Church both split and reformed, rising capitalism was undermining the medieval guild system while growing nationalism was enfeebling the Holy Roman Empire and weakening the papacy.